Understanding the Mechanisms of Achieving Food and Nutritional Security through Traditional Tuber Crops Foods: A Case Study among Konyak Tribes of Nagaland, India - Paramasivan, Sethuraman Sivakumar; A, Thirugnanavel; Chakruno, Martha; Anantharaman, Madavanpillai (JOURNAL OF ROOT CROPS, 2015)
Tropical tuber crops play a crucial role in securing the food and nutritional security of Konyak tribes from remote and backward region of Nagaland, India. Due to their high dry matter content, wide adaptability to soil and climatic conditions and ability to retain quality in semi-processed form for extended storage, tuber crops serve as â€œsecondary staplesâ€ for Konyak community. An exploratory study was conducted among the Konyak tribes of Mon district, Nagaland to document traditional food recipes made from tuber crops and their role in food and nutritional security. A variety of recipes in fresh, dried and fermented forms were prepared from leaves, petioles, tubers/ corms and cormels of tuber crops by blending them with unique localized ingredients. Results revealed that tubers were used both as cereal substitutes and vegetable substitutes during lean season leading to food security. Besides supplying food throughout the year in both fresh and semi-processed form, tuber crops also helped to generate additional income for the tribes.